David Thompson's narrative of his explorations in western America, 1784-182; - Thompson, David, 1770-1857.; Tyrrell, Joseph Burr, 1858-1957. (Toronto, Champlain Society, 1916)
"Pt. II of the narrative covers in detail the years 1807-1812, which were spent as a partner in the North-west company in the provinces of Alberta and British Columbia, and the states of Montana, Idaho, and Washington, while Pt. I. is more general account of his life while in the employ of the Hudson's bay and North-west companies between the years 1784- 1807, in the country from lake Superior and Hudson bay westward to the Rocky mountains." -Pref. No. L16 of 550 copies printed. One map in 4 section in pocket. Series note also on added t.p. "List of works cited": p. 561-565. Mode of access: Internet.